Need Analysis For Designing Learning Materials of Students at Economic And Business Department of Universitas Muhammadiyah Makassar - Wahyuni Sahmar; Andi Tenri Ampa; Bahrun Amin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
The aims of this research were: (1) to find out the content of English Materials need by students of Economic Department Universitas Muhammadiyah Makassar (2) to investigate the reason why students need English materials. This study used descriptive quantitative method. Total Respondents of this research were 37 students of the second semester of Islamic Economic Study Program at Universitas Muhammadiyah Makassar.. The results of this study showed that: first, in the listening Materials, the highest content that students needs is about listen the customer who wants to create an account at Shariah Bank, in the speaking skill, the highest content that students needs is about how to explain to the customer the information in creating an account at Shariah Bank, in the reading materials, the highest content that students’ need is about reading brochure from Islamic bank. And in the writing skill, the highest content that students’ need is materials in the form of reply to letters, emails, and fax from other Islamic Banks, second, There are some reasons why the English materials are needed by Islamic Economic student. first, English materials is important for their future job or career. Second reason is English is international language. The third reason is to be able to communicate orally and written, and the other students said to be able to communicate with tourism.